1998
DOI: 10.1002/(sici)1099-1778(1998100)9:4<215::aid-vis187>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

A spring-mass model-based approach for warping cloth patterns on 3D objects

Abstract: This paper presents a general method for transformations of an object between 2D and 3D which can be used efficiently in computer‐aided garment design. A uniform triangular spring–mass‐based deformable model is employed. Both 2D‐to‐3D and 3D‐to‐2D transformations can be implemented in the same model. An efficient collision detection method is also discussed. © 1998 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Usually the 2D-to-3D transformation is treated as an elastic deformation process with large displacement but small stretch deformation. In [36], a physical based deformable model is proposed for 2D-to-3D sewing and fitting. In this model, the cloth patterns are modeled by a triangular mesh composed of mass nodes and massless edges: edges works as springs.…”
Section: D Pattern Input Virtual Sewing and Fittingmentioning
confidence: 99%
See 3 more Smart Citations
“…Usually the 2D-to-3D transformation is treated as an elastic deformation process with large displacement but small stretch deformation. In [36], a physical based deformable model is proposed for 2D-to-3D sewing and fitting. In this model, the cloth patterns are modeled by a triangular mesh composed of mass nodes and massless edges: edges works as springs.…”
Section: D Pattern Input Virtual Sewing and Fittingmentioning
confidence: 99%
“…Lagrange mechanism is used in [36] to drive the sewing and fitting process. Each node position is determined by the motion of equations:…”
Section: D Pattern Input Virtual Sewing and Fittingmentioning
confidence: 99%
See 2 more Smart Citations
“…Gravitational and even inertial forces can be incorporated into such models. An older survey of such modeling techniques can be found in [1], with more recent research being reported in [2,3,4,5]. A general shape deformation operator tool that could also be used to define wrinkles was discussed in [6].…”
Section: Introductionmentioning
confidence: 99%